Elmer and Rose - McKee, David (North Sydney, NSW : Andersen Press USA, 2010)
When Grandpa Eldo asks Elmer and Wilbur to help a young elephant find her way back to her herd, they are surprised to find that she is pink, but even greater surprises are in store for them.
2.0
K-3
Keywords: Elephants -- Juvenile fiction; Individuality -- Juvenile fiction; Bashfulness -- Juvenile fiction; Elephants -- Fiction; Individuality -- Fiction; Bashfulness -- Fiction; Elephants -- Fiction; Individuality -- Fiction; Shyness -- Fiction; Picture books for children